The Importance of Establishing a Cluster System in Improving the Territorial Structure of the Chemical Industry of Fergana Economic District - Oripovna, Abdinazarova Khidoyatkhon (International Journal of Discoveries and Innovations in Applied Sciences, 2022)
The article focused on the importance of creating a cluster system in improving the territorial structure of the chemical industry in the Fergana economic region. It determines the specialization of the regional chemical industry by calculating the number and territorial share of the population in the territorial units of the economic region, the study of the volume and territorial share of the chemical industry. Based on the studied data, a cluster table was developed and proposed to improve the territorial structure of the economic region chemical industry.